Venezia dei bassifondi: la città dei marginali, della classe operaia e del pittoresco popolare - Alessandro Casellato (Laboratoire Italien)
The paper describes continuity and changes in popular culture in Venice during the first half of the 20th century. It focuses in particular on the use of the city, lifestyles, forms of sociability and political cultures of the urban working-class. It shows how concepts such as “tradition” and “local identity” have been contended and used by different political subjects (the Catholic Church and the Socialist Party in the first two decades of the 20th century, the nazional-fascismo between the two world wars, the Communist Party and again the Catholic Church after World War II).